Digitalization in Education and Student Readiness for Industry 4.0: Critical Analysis and Strategic Recommendations - Rakhmadi, Edy; Norliani, Norliani; Suriansyah, Ahmad; Purwanti, Ratna (Journal of English Language and Education, 2025)
This study critically examines the impact of digitalization in education on students’ readiness to face the transformative demands of the Industrial Revolution 4.0, with specific attention to the Indonesian context. Although international research highlights the role of digital tools in enhancing 21st-century skills, studies in Indonesia remain scarce and often overlook how digital education directly influences student preparedness for Industry 4.0. This gap is particularly urgent given the persistent digital divide, uneven teacher digital competence, and disparities in access to technological infrastructure across Indonesian schools. Adopting a qualitative design, the research employs a triangulation method involving in-depth interviews with five teachers and two students, participatory observation, and document analysis at SMPN 1 Kotabaru. The findings reveal that digitalization significantly enhances student readiness by fostering interactive, personalized, and flexible learning environments. The use of e-learning platforms, AI-based applications, and immersive technologies such as VR/AR not only improves student engagement and self-paced learning but also develops critical competencies, including creativity, communication, collaboration, and critical thinking.This research contributes to filling the gap in Indonesian educational studies by demonstrating how digital transformation can align classroom practices with the competency demands of Industry 4.0. The study provides strategic recommendations for policymakers and educators to strengthen digital infrastructure, improve teacher capacity, and promote inclusive access to technology in order to optimize student readiness for the future world of work.